POSSIBLE CORRELATION BETWEEN CHRONIC TRAMADOL ADMINISTRATION AND DISTURBANCES IN TESTICULAR ACTIVITY AND FERTILITY IN MALE - Mohamed, Mostafa Abd El-Mounem; Elfadaly, Nagy Mohamed; Ibrahim, Shaban Ragab (Journal of medical and pharmaceutical sciences, 2018)
The purpose of this study was used to detect the possible correlation between chronic tramadol administration used at least within the past 12 months and disturbances in testicular activity and fertility in male. The study was involved 100 cases who recruited from toxicological units of Al-Azhar University Hospital (New Damietta). In addition to 20 subjects as a control group. After free informed consent. Extraction of tramadol using a high performance liquid chromatography (HPLC), other blood investigations including semen analysis and finally clinical examination to all groups. Results: There is significant and marked increased in viscosity in (70.0%) and decreased in some semen parameter as (volume, count, motility and progression) were it is (49.0%), (88.0%), (77.0%) and (77.0%) respectively, especially on long term tramadol administration as compared with control group. Conclusion: Significant correlation between tramadol administration and impaired sperm quality parameters in adult males especially on long term tramadol administration as compared with control group. Recommendation: All husband who taken tramadol for a long period especially for premature ejaculation must be recognize about effects of tramadol on fertility as the opposite is true on a long run.